Laundry Business Change Management in Trà Vinh Vietnam: Adaptation to the Covid-19 Pandemic - Hoang, Nguyen Thi (LPPM Universitas Bina Bangsa, 2022)
The purpose of this study is to explore changes in the laundry service business, which is one of the businesses in the service sector that is currently in great demand by boarding housewives and children in Trà Vinh Vietnam City. The research method used is an exploratory method through surveys and in-depth interviews with 15 laundry service businessmen in Tra Vinh City, Vietnam. The survey was conducted in November 2020-April 2021. Where washing clothes through laundry services are considered more efficient and effective. It is believed that this land service will continue to survive, considering that even though washing clothes is a trivial things, this activity requires a lot of time and energy. Practicality is the most basic thing for people who are more active outside the home. By using laundry services, people have more extra time to do other activities. Another thing why laundry services are more effective is because of the need, where there are various types of clothes/items that cannot be washed manually because they require extra attention and special treatment during the washing process. In the era of digitalization, it is also necessary to develop how the laundry service business can survive and develop rapidly so as not to be left behind with similar services. Laundry service owners must dare to make changes for the sake of business development. This change must also be supported by employees, where employees also play an important role in the development of a business, employees who provide good service to consumers give their own impression in the hearts of consumers so that they can make them regular customers